Work environment as mediator between workload and health worker performance - Hamsal Hamsal; Nurman Nurman; Zulfadli Hamzah; Muhammad Arif; Al Sukri (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to investigate the impact of workload on the performance of healthcare workers, both directly and through the mediation of the work environment, at UPTD Puskesmas Batang Gansal. Research Methodology: This study employed a quantitative method using the Structural Equation Modelling (SEM) approach, involving all 103 healthcare workers at UPTD Puskesmas Batang Gansal as a saturated sample. Data were collected through questionnaires, observation, and interviews. The questionnaire employed a Likert scale (1–5), and the data were analysed using SmartPLS 3.0 software. Results: The research findings indicate that workload does not directly affect the performance of healthcare workers, but it significantly impacts the work environment. Additionally, the work environment has been proven to act as a mediator connecting workload and performance, meaning that a conducive work environment can maintain performance even with a high workload. Conclusions: This study shows that workload does not directly affect employee performance, but has an indirect effect through the work environment as a key mediating factor. A supportive work environment enables high performance despite heavy workloads. Limitations: This research is limited to healthcare workers at the Batang Gansal Public Health Centre (UPTD Puskesmas Batang Gansal), with cross-sectional data collected through questionnaires, which makes the results less representative of other institutions and susceptible to subjective bias. Contribution: This research demonstrates that managing workload while improving the work environment is crucial to maintaining productivity.